Biogeography of the social wasp genus Brachygastra (Hymenoptera: Vespidade: Polistinae) - da Silva, Marjorie [UNESP]; Noll, Fernando Barbosa [UNESP] (Wiley, 2015)
Aim: The aim of this study was to understand the biogeography of Brachygastra. As the spatial component of evolution is of fundamental importance to understanding the processes shaping the evolution of taxa, the known geological history of the Neotropical region was used together with the current phylogeny and distribution of species to investigate questions concerning the biogeography of Brachygastra: the ancestral ranges of Brachygastra species; their areal relationships and their congruence with previously published hypotheses; the possible associated vicariance events and the influence of land bridges between North and South America, and the split between the Amazon and Atlantic forests. Location: Neotropical region, from Mexico to central Argentina and southern USA. Methods: Statistical dispersal-vicariance analysis (S-DIVA) was used to reconstruct the possible ancestral ranges of Brachygastra species based on their phylogeny (divided into three groups, lecheguana, scuttelaris and smithii). A Brooks parsimony analysis (BPA) and component analysis were performed to reconstruct the areal relationships of these species within the Neotropics. Results: S-DIVA suggested a widespread, South American ancestral region for Brachygastra. The ancestral B. azteca probably reached the Nearctic before a posterior vicariance event separated it from the species groups ((lecheguana (scutellaris + smithii))), that stayed in the Atlantic forest. The ancestral (scutellaris + smithii groups) possibly reached the Amazon by dispersal, and the subsequent vicariance event splitting the Atlantic forest and Amazon separated the groups into scutellaris in the Atlantic forest and smithii in the Amazon. BPA and component analyses suggested that the Nearctic was a sister area to other regions, the Andes and Mesoamerica was a sister area to the Neotropical regions and the Amazon was closely related to the Atlantic forest. Main conclusions: The phylogeny and distribution of Brachygastra suggest the influence of a land bridge between the Northern and Southern Hemispheres affecting the cladogenesis of B. azteca and the importance of the formation of the two blocks of forests in South America to the cladogenesis of the main groups of Brachygastra. Future comparisons between the distribution patterns of other taxa should enable a more precise identification of the possible events and outcomes, adding robustness to the hypothesized areal relationships.
Keywords: Brachygastra; Cladistic biogeography; Epiponini; Historical biogeography; Neotropical region; S-DIVA; Vicariance